Divorce Caused by Impotence According to Ibn Hazm (Analysis of the Decision of the Judge of the Syar'iyah Court of Banda Aceh City Number 434/Pdt.G/2020/Ms.Bna): Perceraian Disebabkan Impotensi Menurut Ibnu Hazm (Analisis Putusan Hakim Mahkamah Syar’iyah Kota Banda Aceh Nomor 434/Pdt.G/2020/Ms.Bna) - Novianti, Novianti (El-Hadhanah : Indonesian Journal Of Family Law And Islamic Law, 2021)
Divorce has its own reasons. Among them because of shiqaq, violence, and others. But in fact, divorce can be done due to shiqaq for reasons of sexual dysfunction (impotence). This study specifically analyzes the Banda Aceh Syar'iyah Court Decision Number 434/Pdt.G/2020/Ms.Bna. If we review it based on Ibn Hazm's opinion, then the decision Number 434/Pdt.G/2020/Ms.Bna is very contradictory because impotence should not be used as a reason for divorce for married couples. The purpose of this research is to know that divorce is caused by impotence according to Ibnu Hazm, and to know the decision of the Banda Aceh Syar'iyah Court Judge Number 434/Pdt.G/2020/Ms.Bna in Ibnu Hazm's perspective. This research was conducted using a normative legal approach with library research. The data collected was studied through descriptive analysis methods and comparative methods. The results of the research analysis show that: First, Ibn Hazm argues that marriage cannot be legalized because of a defect or disgrace to the husband or wife. Ibn Hazm only admits that there are only eight types of marriage that can lead to marriage. For this reason, the marriage will continue until there are other causes as a way of separation. He only accepted the Faskh if ​​the hadiths were authentic, Ibn Hazm rejected the Faskh marriage on the grounds of a defect because there is no valid evidence or text in the Al-Quran, Sunnah, Ijmak, Qiyas or logic that allows the Fasach. Second, Judge MS. Bna saw that in the household there were often quarrels and disputes because the Defendant had sexual dysfunction (impotence) which caused the Defendant to be unable to provide spiritual support to the Plaintiff as husband and wife should. The family has reconciled, but the hope of living together is no longer there. Meanwhile, Ibn Hazm's view on the case was that he did not allow the judge to facilitate or give time for the marriage, but Ibn Hazm allowed it if it was the husband who dropped the thalaq on his wife.